PROBABILITY PUTUSAN SENGKETA BANDING DI BIDANG KEPABEANAN - Purwana, Aditya Subur; Rachman, Mirza Chaidir; Pahlevi, Yonathan Agung; Syamsuddin, Muhammad Anshar (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
Customs services are self-assessment in nature, but as supervisory authority DGCE carries out official assessments in the form of determining Customs and Excise Officials. Which can be grouped into 2 (two) main categories, namely (i) determination of Customs and Excise Officials which causes underpayment and/or administrative sanctions, and (ii) determination of Customs and Excise Officials regarding provisions on prohibited and/or Restricted goods or on the determination of State Controlled Goods. Legal objections and/or appeals can be made to the customs excise determination. The aim of the research is to measure the probability of legal action decisions in the customs sector, using descriptive statistics and logistic regression. The data used is secondary from 2021 to 2021. May 2024. The research results show that the probability of an appeal decision in the DGCE category winning is greater than that of DGCE losing, while the probability of an appeal decision for DGCE winning and DGCE losing is almost the same. Keywords : Appeals, Objections, Customs, Legal Remedies